Unmanned ground vehicle for covid-19 waste management - Roshahliza, M. Ramli; Mohd Azrul Hisham, Mohd Adib; Idris, Mat Sahat; Nurul Aqilah, Herman; Mohamad Syazwan, Mohd Roni; Amirul Hafiz, Zexafiza (2021)
To design a robot that can lift mask and sanitize by its own to reduce COVID-19 spreadness.